Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate, electrode and electric device
By depositing high-crystalline silicon particles on the porous carbon matrix and forming a carbon cladding layer, the problem that existing silicon carbon anode materials cannot take into account high first-time Coulomb efficiency and good cycle stability in batteries is solved, and the battery is taken into account in terms of capacity, Coulomb efficiency and cycle performance.
Patent Information
- Application Number
- CN202311523761.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2025-04-18
AI Technical Summary
Existing silicon-carbon anode materials cannot take into account high first-time Coulomb efficiency and good cycle stability in batteries.
Using porous carbon as the matrix, silicon particles with high crystallinity and small grain size are deposited, and a carbon cladding is formed on the surface to improve the cycling performance of the battery and the first-time Coulomb efficiency.
By improving the crystallinity of silicon particles and controlling their grain size, the cycle stability and first-time Coulomb efficiency of the battery are enhanced, and the battery is taken into account in terms of capacity, Coulomb efficiency and cycling performance.
Smart Images

Figure CN119852337A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet, an electrode and an electrical device. Background Art
[0002] Silicon is a high-capacity material that can be used as anode material. Its theoretical capacity can reach more than 10 times that of the current mainstream graphite anode. Silicon is highly safe, has abundant resources and low production costs. Carbon materials have high electrical conductivity, relatively stable structure, small volume expansion during the cycle, usually less than 10%, and good flexibility and lubricity. If silicon-carbon anode materials can combine the advantages of both, the performance of secondary batteries can be greatly improved.
[0003] However, although the capacity of the current gas-phase synthesized silicon-carbon materials is improved compared to traditional technologies, the first coulombic efficiency is low. In order to improve the first coulombic efficiency of the silicon-carbon negative electrode material, there is a defect of sacrificing cycle stability. That is, after the existing silicon-carbon negative electrode material is used in the battery, it is impossible to achieve both better cycle stability and high first coulombic efficiency. Summary of the invention
[0004] In view of the above problems, the present application proposes a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode plate, an electrode and an electrical device, which can improve the technical problem that the battery cannot obtain both good cycle stability and high first coulomb efficiency.
[0005] In a first aspect, an embodiment of the present application provides a silicon-carbon negative electrode material, which includes porous carbon and silicon particles attached to the pore walls of the porous carbon, wherein a crystalline phase exists in the silicon particles and the crystallinity is at least 90%, and the average grain size of the silicon particles is less than 4 nm.
[0006] In the silicon-carbon negative electrode material provided by the present application, since there is a crystalline phase (that is, crystalline silicon) in the silicon particles and the degree of crystallinity is at least 90%, the first coulombic efficiency of the battery can be effectively improved compared to amorphous silicon. The silicon particles are attached to the pore walls of the porous carbon and the average grain size of the silicon particles is less than 4nm. On the one hand, the average grain size of the silicon particles is limited to alleviate and reduce the difference in expansion force of crystalline silicon in all directions, which is beneficial to alleviate and improve the cycle stability of the battery. On the other hand, a part of the space can be reserved in the pores to buffer the volume expansion caused by the silicon particles, which can further improve the cycle performance of the battery using this negative electrode material.
[0007] That is, the silicon-carbon negative electrode material provided in the present application can enable the battery to obtain both better cycle stability and high first coulombic efficiency.
[0008] In some embodiments, the average grain size of silicon particles is less than 2 nm. Within the above range, it is beneficial to reduce the difference in expansion force of crystalline silicon in various directions, which is beneficial to further improve the cycle performance of the battery.
[0009] In some embodiments, the average pore size of the porous carbon is ≤4 nm, and can be ≤2 nm, which is beneficial to improving the cycle performance of a battery using such a negative electrode material.
[0010] In some embodiments, the porous carbon satisfies at least one of the following characteristics:
[0011] (a1) The porous carbon has micropores, mesopores and macropores, and the volume proportion of micropores is ≥75%;
[0012] (a2) The specific surface area of porous carbon is ≥1700m 2 / g;
[0013] (a3) The pore volume of porous carbon is ≥ 0.75 m 3 / g;
[0014] Optionally, the porous carbon satisfies at least one of the following characteristics:
[0015] (b1) The porous carbon has micropores, mesopores and macropores, and the volume proportion of micropores is ≥85%;
[0016] (b2) The specific surface area of porous carbon is ≥1800m 2 / g;
[0017] (b3) The pore volume of porous carbon is ≥ 0.8 m 3 / g.
[0018] Within the above range, the battery using the negative electrode material can achieve better capacity, coulombic efficiency and cycle performance.
[0019] In some embodiments, porous carbon and silicon particles are used as the main body, and the silicon-carbon negative electrode material also includes a carbon coating layer coated on the main body. The carbon coating layer is wrapped on the surface of the main body, which, on the one hand, seals the pores to make them closed pores, so that the external electrolyte cannot enter the internal pores, and reduces the specific surface area, reduces the loss of active lithium when the SEI film is formed on the surface of the silicon-carbon negative electrode material, and on the other hand, prevents the capacity loss caused by the oxidation of silicon on the surface of the material, resulting in a decrease in the first coulomb efficiency of the battery.
[0020] In some embodiments, the carbon coating layer is a discontinuous coating, and the thickness of the carbon coating layer is 1-40 nm.
[0021] In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following characteristics:
[0022] (c1) The mass content of silicon particles in the silicon-carbon negative electrode material is 35% to 55%;
[0023] (c2) The porosity of the silicon-carbon negative electrode material is 40% to 60%;
[0024] (c3) The specific surface area of silicon-carbon negative electrode material is ≤ 6m 2 / g;
[0025] (c4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 4 μm to 15 μm.
[0026] Within the above range, it is beneficial for the battery using such negative electrode material to have better capacity, coulombic efficiency and cycle performance. In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following characteristics:
[0027] (d1) The mass content of silicon particles in the silicon-carbon negative electrode material is 40% to 50%;
[0028] (d2) The porosity of the silicon-carbon negative electrode material is 45% to 55%;
[0029] (d3) The specific surface area of silicon-carbon negative electrode material is ≤4m 2 / g;
[0030] (d4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 5 μm to 10 μm.
[0031] Within the above range, the battery using the negative electrode material can achieve better capacity, coulombic efficiency and cycle performance.
[0032] In a second aspect, the present application provides a method for preparing the silicon-carbon negative electrode material in the above-mentioned embodiment, which comprises: depositing silicon particles on porous carbon by chemical vapor deposition; wherein the average pore size of the porous carbon is ≤4 nm.
[0033] In the technical solution of the embodiment of the present application, silicon particles are deposited on porous carbon by chemical vapor deposition. The silicon particles are deposited in the pores of the porous carbon. Therefore, the maximum grain size of the silicon particles is < the pore size of the porous carbon, and the average grain size of the silicon particles is < the average pore size of the porous carbon. Therefore, the average pore size of the porous carbon is ≤4nm, so that the average grain size of the silicon particles can be controlled to be <4nm, so that after the prepared silicon-carbon negative electrode material is applied to the battery, the battery has both good cycle stability and high first coulombic efficiency.
[0034] In some embodiments, the method of depositing silicon particles on porous carbon by chemical vapor deposition includes:
[0035] The porous carbon is placed in a reaction atmosphere and kept warm at 400°C to 550°C for at least 8 hours, wherein the reaction atmosphere is a mixed atmosphere of a protective gas and a silicon source gas, the gas flow ratio of the protective gas to the silicon source gas is 90:10 to 70:30, and the protective gas includes at least one of an inert gas and hydrogen; by adjusting the temperature, gas ratio and holding time within the above range to control the decomposition efficiency and deposition rate of the silicon source gas, on the one hand, it is beneficial for the silicon particles to be evenly distributed in the pores of the porous carbon, and on the other hand, it is beneficial for the generation of crystalline silicon and for suppressing the generation of silicon carbide without capacity or excessive amorphous silicon.
[0036] Optionally, the temperature of the heat preservation reaction is 430°C to 530°C.
[0037] Optionally, the gas flow ratio of the protective gas to the silicon source gas is 85:15 to 75:25.
[0038] Optionally, the insulation reaction time is 8 hours to 16 hours, and optionally 10 hours to 16 hours.
[0039] In some embodiments, the preparation method further comprises: the preparation method further comprises: using a product obtained by depositing silicon particles on porous carbon as a body, placing the body in a mixed atmosphere of a carbon source and an inert gas, and pyrolyzing the carbon source to form a carbon coating layer coated on the body;
[0040] The carbon source includes one or more of alkanes, alkynes and alkenes.
[0041] Through the above arrangement, a uniformly distributed carbon coating layer can be formed on the surface of the body, thereby improving the stability of the material interface and reducing the specific surface area, which is beneficial for the battery to have both better first coulomb efficiency and better cycle performance.
[0042] Optionally, the temperature of the pyrolysis carbon source is 400°C to 800°C, and the pyrolysis time is 0.2h to 2h;
[0043] Optionally, the gas flow ratio of the inert gas to the carbon source is 1:(1.5-5).
[0044] In a third aspect, the present application provides a negative electrode plate, which includes the silicon-carbon negative electrode material in the above embodiment.
[0045] In a fourth aspect, the present application provides a battery, which includes the battery cell in the above embodiment.
[0046] In a fifth aspect, the present application provides an electrical device, which includes the battery in the above embodiment, and the battery is used to provide electrical energy.
[0047] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0049] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;
[0050] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;
[0051] Figure 3 A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;
[0052] Figure 4 This is a schematic diagram of the structure of the negative electrode sheet of some embodiments of the present application;
[0053] Figure 5 XRD diagram of the silicon-carbon negative electrode material provided in Example 1;
[0054] Figure 6 XRD diagram of the silicon-carbon negative electrode material provided in Comparative Example 1;
[0055] Figure 7 This is the XRD diagram of the silicon-carbon negative electrode material provided for Comparative Example 2.
[0056] The reference numerals in the specific implementation manner are as follows:
[0057] 1000-Vehicles;
[0058] 100-battery; 200-controller; 300-motor;
[0059] 10-box; 11-first part; 12-second part;
[0060] 20-battery cell; 21-housing; 22-electrode assembly; 23-electrode terminal; 24-pressure relief structure;
[0061] 211-housing; 212-cover;
[0062] 221 - negative electrode plate; 2211 - negative electrode current collector; 2212 - negative electrode tab; 2213 - negative electrode active material layer. DETAILED DESCRIPTION
[0063] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0064] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0065] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0066] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0067] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0068] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0069] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0070] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0071] In order to alleviate the problem that batteries using existing silicon-carbon negative electrode materials cannot take into account both good cycle stability and high first coulombic efficiency, the present application designs a silicon-carbon negative electrode material, which includes porous carbon and silicon particles attached to the pore walls of the porous carbon, wherein a crystalline phase exists in the silicon particles and the degree of crystallinity is at least 90%, and the average grain size of the silicon particles is less than 4nm.
[0072] In such a silicon-carbon negative electrode material, since there is a crystalline phase (that is, crystalline silicon) in the silicon particles and the degree of crystallinity is at least 90%, the first coulombic efficiency of the battery can be effectively improved compared to amorphous silicon. The average grain size of the silicon particles is less than 4nm, which can effectively improve the cycle stability of the battery. The silicon particles are attached to the pore walls of the porous carbon so that a part of the space can be reserved in the pores to buffer the volume expansion caused by the silicon particles, which can further improve the cycle performance of the battery.
[0073] The battery disclosed in the embodiment of the present application can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft. A power supply system having the battery disclosed in the present application and the like to form the electrical device can be used, which is conducive to alleviating and improving the initial coulombic efficiency and cycle performance of the battery.
[0074] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0075] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0076] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0077] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0078] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may also include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0079] Please refer to Figure 2 , Figure 2An exploded view of a battery 100 provided in some embodiments of the present application. The battery 100 includes a box 10 and a battery cell 20, and the battery cell 20 is contained in the box 10. Among them, the box 10 is used to provide a storage space for the battery cell 20, and the box 10 can adopt a variety of structures. In some embodiments, the box 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, the first part 11 may be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box 10 formed by the first part 11 and the second part 12 may be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0080] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.
[0081] The battery cell 20 refers to the smallest unit constituting the battery 100. The battery cell 20 may be a lithium ion battery.
[0082] Please refer to Figure 3 , Figure 3 This is a schematic diagram of the exploded structure of a battery cell 20 provided in some embodiments of the present application. Figure 3 The battery cell 20 may include a housing 21 , an electrode assembly 22 and an electrolyte, and both the electrode assembly 22 and the electrolyte are contained in the housing 21 .
[0083] The housing 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space of the battery cell 20, wherein the formed sealed space can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.
[0084] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The shell 211 and the cover 212 can be made of various materials, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The sealing ring can be made of various materials, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.
[0085] The battery cell 20 may also be in a soft pack form, such as a bag-type soft pack. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0086] The electrode assembly 22 includes a negative electrode sheet, a separator and a positive electrode sheet. The battery cell 20 mainly relies on the movement of metal ions between the positive electrode sheet and the negative electrode sheet to work. During the charge and discharge process, the active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet; the separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly prevents the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The electrode assembly 22 can be a winding structure or a stacked structure, and the embodiments of the present application are not limited to this.
[0087] The positive electrode sheet includes a positive electrode collector, a positive electrode ear and a positive electrode active material layer. The positive electrode active material layer is arranged on at least one side of the positive electrode collector. A primer layer or the like may also be arranged between the positive electrode active material layer and the positive electrode collector. The positive electrode ear protrudes from the positive electrode collector. The positive electrode ear is located at one end or two opposite ends of the positive electrode collector, for example.
[0088] Among them, the positive electrode current collector can be a metal foil or a composite current collector, for example, the material of the positive electrode current collector and the positive electrode tab can be aluminum. The composite current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base, and the composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0089] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0090] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0091] The isolation membrane is located between the positive electrode plate and the negative electrode plate and plays an isolation role. The embodiment of the present application has no particular restriction on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0092] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0093] like Figure 4 As shown, the negative electrode plate 221 includes a negative electrode collector 2211, a negative electrode tab 2212 and a negative electrode active material layer 2213, the negative electrode active material layer 2213 is arranged on at least one side of the negative electrode collector 2211, and a primer layer or the like may be further arranged between the negative electrode collector 2211 and the negative electrode active material layer 2213; the negative electrode tab 2212 protrudes from the negative electrode collector 2211, and the negative electrode tab 2212 is, for example, located at one end or two opposite ends of the negative electrode collector 2211.
[0094] Among them, the negative electrode current collector 2211 can be made of metal foil or a composite current collector. For example, the material of the negative electrode current collector 2211 and the negative electrode tab 2212 can be copper. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0095] The negative electrode active material in the negative electrode active material layer 2213 includes a silicon-carbon negative electrode material.
[0096] In some embodiments, the negative electrode active material layer 2213 may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0097] In some embodiments, the negative electrode active material layer 2213 may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0098] In some embodiments, the negative electrode active material layer 2213 may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0099] The silicon-carbon negative electrode material and the preparation method thereof proposed in the embodiments of the present application are described in detail below in conjunction with the accompanying drawings.
[0100] According to some embodiments of the present application, the silicon-carbon negative electrode material includes porous carbon and silicon particles attached to the pore walls of the porous carbon, the silicon particles contain a crystalline phase and have a crystallinity of at least 90%, and the average grain size of the silicon particles is less than 4 nm.
[0101] Porous carbon includes but is not limited to graphite, soft carbon, hard carbon and other porous carbons.
[0102] Silicon particles attached to the pore walls of porous carbon means that silicon particles are attached to the pore walls of porous carbon and the pore space is not filled with silicon particles. That is, the porous carbon with silicon particles attached to the pore walls still has certain pores.
[0103] The presence of a crystalline phase in the silicon particles and a crystallinity of at least 90% means that: the silicon particles are all crystalline phases, in which case the silicon particles are all crystalline silicon, or the silicon particles are a mixture of a crystalline phase and an amorphous phase, in which the mass proportion of the crystalline phase is at least 90%. The crystallinity can be calculated by the characteristic peak of silicon in the Raman spectrum of the silicon-carbon negative electrode material. Specifically, the crystallinity can be calculated by dividing the area of the Raman peak representing the crystalline silicon in the silicon particles by the area of the Raman peak representing the total silicon including the crystalline phase and the amorphous phase in the silicon particles.
[0104] Illustratively, the crystallinity is any value of 90%, 92%, 93%, 95%, 96%, 97%, 98%, 99%, 100%, or between any two values.
[0105] The average grain size of the silicon particles here refers to the average size of the crystalline silicon in the silicon particles. Since there is a crystalline phase in the silicon particles and the degree of crystallinity is at least 90%, that is, most of them are crystalline silicon, crystalline silicon is anisotropic when it expands. Therefore, the average grain size of the silicon particles is less than 4nm to alleviate the anisotropy of the crystalline silicon when it expands.
[0106] The average grain size of silicon particles can be calculated based on the XRD pattern of the sample tested according to the JIS / K0131~1996 test standard. According to the XRD pattern of the sample, the half-peak width β and the diffraction angle θ of the Si (111) crystal plane diffraction peak are taken and substituted into the Debye~Scherrer formula to calculate the average grain size of the silicon particles.
[0107] Debye-Scherrer formula: Dhkl=kλ / βcosθ, where Dhkl is the average grain size of silicon particles, in nm; k is the Scherrer constant, 0.89; λ is the wavelength of incident X-rays, 0.15406 nm; β is the half-peak width of the diffraction peak, in rad; θ is the diffraction angle, in degrees.
[0108] Illustratively, the average grain size of the silicon particles includes but is not limited to any value of 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 3.9 nm, etc.
[0109] In the silicon-carbon negative electrode material provided by the present application, since there is a crystalline phase (that is, crystalline silicon) in the silicon particles and the degree of crystallinity is at least 90%, the first coulombic efficiency of the battery can be effectively improved compared to amorphous silicon. The silicon particles are attached to the pore walls of the porous carbon and the average grain size of the silicon particles is less than 4nm. On the one hand, the average size limitation is utilized to alleviate and reduce the difference in expansion force of crystalline silicon in all directions, which is beneficial to alleviate and improve the cycle stability of the battery. On the other hand, a part of the space can be reserved in the pores to buffer the volume expansion caused by the silicon particles, which can further improve the cycle performance of the battery.
[0110] That is, the silicon-carbon negative electrode material provided in the present application can enable the battery to obtain both better cycle stability and high first coulombic efficiency.
[0111] In some embodiments, the average grain size of the silicon particles is <2 nm.
[0112] Within the above range, it is beneficial to further reduce the difference in expansion force of crystalline silicon in various directions, which is beneficial to improving the cycle performance of the battery.
[0113] In some embodiments, the porous carbon has an average pore size of ≤ 4 nm.
[0114] Porous carbon can be divided into crack pores, conical pores, cylindrical pores, spherical pores, etc. according to the pore shape, and some pores are irregular, so the pore size here is defined as the distance between the two farthest points on the pore wall of the pore.
[0115] It can be understood that the arrangement in which the silicon particles are attached to the pore walls of the porous carbon, that is, the pore size of the porous carbon is utilized, is conducive to limiting the size of the silicon grains. The maximum grain size of the silicon particles is bound to be smaller than the pore size of the porous carbon, and the average grain size of the silicon particles is also smaller than the average pore size of the porous carbon, thereby leaving a certain amount of space after deposition to alleviate expansion.
[0116] Therefore, by using the average pore size of porous carbon ≤4nm, on the one hand, the average grain size of silicon particles can be effectively limited to <4nm, which is beneficial to improving the cycle performance. On the other hand, under the same volume, the larger the pore size, the lower the porosity, resulting in concentrated distribution of pores. Therefore, when the average pore size of porous carbon is ≤4nm, the pores on the porous carbon are basically evenly distributed, which is beneficial to the uniform distribution of silicon particles in the silicon-carbon negative electrode material, thereby improving the cycle performance of the battery.
[0117] Optionally, the average pore size of the porous carbon is ≤2 nm.
[0118] Within the above range, the average grain size of silicon particles can be effectively limited to less than 2 nm, and it is beneficial to uniformly distribute silicon particles in the silicon-carbon negative electrode material, thereby helping to improve the cycle performance of the battery.
[0119] In some embodiments, the porous carbon satisfies at least one of the following characteristics:
[0120] (a1) The porous carbon has micropores, mesopores and macropores, and the volume proportion of micropores is ≥75%.
[0121] Micropores, mesopores and macropores are distinguished according to the pore size. Among them, pores with a diameter less than 2nm are called micropores; pores with a diameter greater than 50nm are called macropores; and pores with a diameter between 2 and 50nm are called mesopores (or mesopores).
[0122] The more holes there are, the larger the corresponding pore volume is. Therefore, the volume percentage is used to reflect the number of micropores, that is, the micropore percentage is based on the average pore size, which further limits the number of micropores. From the description of the pore size distribution, it can be seen that micropores can better limit the size of silicon particles and promote the uniform distribution of silicon within the material. Therefore, using a micropore volume percentage of ≥75% is beneficial to further improve expansion and enhance the cycle performance of the battery.
[0123] Illustratively, the volume percentage of the micropores includes but is not limited to any value of 75%, 80%, 85%, 90%, 95%, etc.
[0124] (a2) The specific surface area of porous carbon is ≥1700m 2 / g.
[0125] The above specific surface area range is conducive to the deposition of silicon particles in the pores of the porous carbon, thereby improving the initial discharge capacity and cycle performance of the battery.
[0126] (a4) The pore volume of porous carbon is ≥ 0.75 m 3 / g.
[0127] The pore volume refers to the total volume of pores per unit mass of porous carbon, and the pore volume of porous carbon corresponds to the deposition amount of silicon particles.
[0128] By limiting the pore volume of porous carbon to >0.75 m 3 / g, it is beneficial to deposit a target amount of silicon in the porous carbon to increase the capacity of the silicon-carbon negative electrode material, and after the silicon is deposited to the target amount, the porous carbon still has sufficient pores to buffer the volume expansion caused by the silicon particles, thereby improving the initial discharge capacity and cycle performance of the battery.
[0129] In some embodiments, the porous carbon satisfies at least one of the following characteristics:
[0130] (b1) Porous carbon has micropores, mesopores and macropores, and the volume proportion of micropores is greater than 85%;
[0131] The volume proportion of micropores is greater than 85%, which helps to evenly distribute silicon within the material, thereby improving expansion and enhancing cycle performance.
[0132] (b2) Specific surface area of porous carbon>1800m 2 / g;
[0133] Within the above specific surface area range, silicon particles are conducive to the deposition in the pores of porous carbon, further improving the capacity and cycle performance of the battery.
[0134] (b3) The pore volume of porous carbon is > 0.8 m 3 / g.
[0135] Within the above range, it is beneficial to further improve the capacity and cycle performance of the battery.
[0136] In some embodiments, porous carbon and silicon particles are used together as a main body, and the silicon-carbon negative electrode material further includes a carbon coating layer coated on the main body.
[0137] Since silicon particles are highly active, a carbon coating layer is used to wrap the surface of the body. On the one hand, the pores are sealed to make them closed pores, so that the external electrolyte cannot enter the internal pores, and the specific surface area is reduced, thereby reducing the loss of active lithium when the SEI film is formed on the surface of the silicon-carbon negative electrode material. On the other hand, it can prevent the capacity loss caused by the oxidation of silicon on the surface of the material, which leads to a decrease in the first coulombic efficiency of the battery.
[0138] In some embodiments, the carbon coating layer is a discontinuous coating, and the thickness of the carbon coating layer is 1 to 40 nm.
[0139] Exemplarily, the thickness of the carbon layer is tested by embedding and curing the negative electrode active material with epoxy resin, and then using ultrathin sectioning to cut the material into a size of 50nm to 70nm, and prepare the sample. Use a high-power transmission electron microscope to select the section of the particle sample for observation, observe the pore area and the disordered carbon layer area, the pore area and the disordered carbon layer area are the body, and the outermost disordered part of the entire body is the carbon shell. The material is photographed and observed by TEM, and then the image analysis software Image J is used to randomly select 10 negative electrode material particles from the photo to obtain the thickness of the outermost disordered part (carbon coating layer) of these negative electrode material particles, and then the average thickness of the 10 negative electrode material particles is taken as the thickness of the carbon coating layer.
[0140] Within the above thickness range, lithium can diffuse through the carbon coating layer and can effectively coat the body.
[0141] In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following characteristics:
[0142] (c1) The mass content of silicon particles in the silicon-carbon negative electrode material is 35-55%;
[0143] The silicon content determines the capacity of the material. Too low a silicon content will result in low material capacity, but too high a silicon content will also result in low residual porosity and will not be able to control the expansion of the silicon-carbon negative electrode material well.
[0144] Therefore, the silicon carbon negative electrode material uses a silicon particle content of 35-55% by mass, which can improve the battery's initial discharge capacity, cycle performance and initial coulombic efficiency.
[0145] Exemplarily, the mass content of silicon particles in the silicon-carbon negative electrode material is any value of 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53%, 55%, or between any two values.
[0146] (c2) The porosity of the silicon-carbon negative electrode material is 40% to 60%;
[0147] If the porous carbon with the same parameters has a low porosity, the expansion control cannot be achieved well, thus affecting the material's cycle performance. If the porosity is too high, on the one hand, the silicon-carbon negative electrode material will have a low capacity due to the small amount of silicon deposition, and on the other hand, the structure will be unstable, and the silicon-carbon negative electrode material will be at risk of being cracked during cold pressing. Therefore, the use of a silicon-carbon negative electrode material with a porosity of 40% to 60% can give the battery a better capacity, cycle performance and high first coulombic efficiency.
[0148] Exemplarily, the porosity of the silicon-carbon negative electrode material is any value of 40%, 43%, 45%, 47%, 50%, 53%, 55%, 57%, 60%, or between any two values. (c3) The specific surface area of the silicon-carbon negative electrode material is ≤ 6m 2 / g;
[0149] By controlling the specific surface area of silicon-carbon negative electrode materials to ≤6m 2 / g, to avoid excessive loss of active lithium when SEI film is formed on the surface of silicon-carbon negative electrode material due to excessive specific surface area, resulting in low initial coulombic efficiency of the battery and deterioration of cycle performance.
[0150] Exemplarily, the specific surface area of the silicon-carbon negative electrode material includes but is not limited to 6 m 2 / g, 5m 2 / g, 4m 2 / g, 3m 2 / g, 2m 2 / g, 1m 2 / g or 0.5m 2 / g, etc.
[0151] (c4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 4 μm to 15 μm.
[0152] The volume particle size distribution Dv50 refers to a particle size distribution parameter determined by a particle size distribution measurement value. For example, the volume particle size distribution Dv50 is determined using a particle size analyzer-laser diffraction method. Specifically, the standard GB / T 19077-2016 can be referred to and a laser diffraction scattering particle size analyzer can be used for measurement.
[0153] Within the above range, the battery is beneficial to have better cycle performance, first coulomb efficiency and fast charging performance.
[0154] Exemplarily, the volume particle size distribution Dv50 of the silicon-carbon negative electrode material is any value of 4 μm, 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 13 μm, 15 μm or between any two values.
[0155] In some embodiments, the silicon-carbon negative electrode material satisfies at least one of the following characteristics:
[0156] (d1) The mass content of silicon particles in the silicon-carbon negative electrode material is 40% to 50%;
[0157] (d2) The porosity of the silicon-carbon negative electrode material is 45% to 55%;
[0158] (d3) The specific surface area of silicon-carbon negative electrode material is less than 4m 2 / g;
[0159] (d4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 5 μm to 10 μm.
[0160] By limiting the above parameters, it is beneficial to improve the battery capacity, cycle performance and first coulombic efficiency at the same time.
[0161] In some embodiments, the present application also provides a method for preparing the above silicon-carbon negative electrode material, which comprises: depositing silicon particles on porous carbon by chemical vapor deposition;
[0162] Among them, the average pore size of the porous carbon is ≤4nm.
[0163] In the above preparation method, silicon particles are deposited on porous carbon by chemical vapor deposition. The silicon particles are deposited in the pores of the porous carbon. Therefore, the maximum grain size of the silicon particles is < the pore size of the porous carbon, and the average grain size of the silicon particles is < the average pore size of the porous carbon. Therefore, the average pore size of the porous carbon is ≤4nm, so that the average grain size of the silicon particles can be controlled to be <4nm. After the prepared silicon-carbon negative electrode material is applied to the battery, the battery has both better cycle stability and high first coulombic efficiency.
[0164] In some embodiments, the method of depositing silicon particles on porous carbon by chemical vapor deposition includes:
[0165] The porous carbon is placed in a reaction atmosphere and kept warm at 400°C to 550°C for at least 8 hours, wherein the reaction atmosphere is a mixed atmosphere of a protective gas and a silicon source gas, the gas flow ratio of the protective gas to the silicon source gas is 90:10 to 70:30, and the protective gas includes at least one of an inert gas and hydrogen.
[0166] Inert gases include but are not limited to nitrogen, argon, and the like.
[0167] The silicon source gas includes but is not limited to one or more silane-containing hydrocarbons such as silane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0168] It can be understood that the method of depositing silicon particles on porous carbon by chemical vapor deposition can be carried out in the heating chamber of a vapor deposition furnace. The porous carbon can be placed in the heating chamber of the vapor deposition furnace first, and then the heating chamber can be evacuated by a vacuum pump. Then, an inert gas is introduced into the heating chamber to avoid interference from impurities. After the inert gas fills the heating chamber, a mixed gas is introduced at a ratio of 90:10 to 70:30 between protective gas and silicon source gas. While introducing the mixed gas, the temperature of the heating chamber of the vapor deposition furnace is raised to 400°C to 550°C, so that the silicon source gas decomposes silicon and is deposited in the pores of the porous carbon. The mixed gas is continuously introduced into the heating chamber of the vapor deposition furnace, and the pressure in the heating chamber of the vapor deposition furnace is maintained at normal pressure for at least 8 hours of insulation reaction.
[0169] Among them, if the proportion of silicon source gas in the mixed gas is too high, the silicon deposition rate will be too fast, the nano silicon particles are easy to agglomerate, and the agglomerated silicon particles are easy to block the pores, resulting in less silicon deposition in the center of the porous carbon, thereby affecting the uneven distribution of internal silicon particles, resulting in large local expansion of the silicon-carbon negative electrode material during the cycle, easy to crack and break, affecting the structural stability of the silicon-carbon negative electrode material, and if the proportion of silicon source gas in the mixed gas is too low, the deposition rate will be too slow and the process efficiency will be too low. Therefore, the gas flow ratio of the protective gas and the silicon source gas is 90:10 to 70:30. Exemplarily, the gas flow ratio of the protective gas and the silicon source gas is any value of 90:10, 89:11, 85:15, 83:17, 80:20, 77:23, 75:25, 73:27, 71:29, 70:30 or between any two values.
[0170] The holding temperature affects the decomposition of the silicon source gas and the components obtained. 400°C is the temperature at which the silicon source gas begins to decompose amorphous silicon. If the temperature is too low, silane cannot be decomposed and the silicon deposition process cannot be carried out. If the temperature is too high, on the one hand, the decomposition speed is too fast, which can easily cause pore blockage and uneven distribution of silicon inside the material. On the other hand, if the temperature is too high, nano-silicon and carbon substrates react to produce silicon carbide, which cannot provide capacity, resulting in material capacity loss. Therefore, the holding temperature is 400°C to 550°C. Exemplarily, the temperature of the holding reaction is any value of 400°C, 430°C, 450°C, 460°C, 470°C, 500°C, 530°C, and 550°C, or between any two values.
[0171] Since the silicon-carbon negative electrode material mainly relies on silicon particles to provide capacity, if the holding time is too short, the amount of deposited silicon particles will be small, and the capacity of the silicon-carbon negative electrode material will be low. If the holding time is too short, it will be not conducive to the formation of crystalline silicon. If the holding time is too long, too many silicon particles will be deposited. On the one hand, the residual porosity of the silicon-carbon negative electrode material will be low, which cannot meet the demand of reserved pores to reduce expansion. On the other hand, when the pores are full of nano-silicon particles, silicon will be deposited on the surface of the material to form a silicon-rich layer. The silicon on the surface is not within the limit of the porous carbon substrate framework, and its expansion is not restricted. Therefore, there is a large expansion during the cycle, and the surface of the material is prone to cracking to form a thicker by-product layer. Once the by-product layer is too thick, the silicon-carbon negative electrode material will lose its activity and no longer participate in the cycle process, thereby affecting the cycle performance. Therefore, the holding time is at least 8h.
[0172] In the chemical vapor deposition method provided in the present application, since the pore size of the porous carbon used is relatively small, it is necessary to control the decomposition efficiency and deposition rate of the silicon source gas by adjusting the temperature, gas ratio and insulation time within the above range. On the one hand, it is beneficial to the uniform distribution of silicon particles in the pores of the porous carbon, and on the other hand, it is beneficial to the generation of crystalline silicon while suppressing the generation of capacity-less silicon carbide or excessive amorphous silicon.
[0173] In some embodiments, the temperature of the insulation reaction is 430°C to 530°C.
[0174] The above range is conducive to the formation of crystalline silicon, which is beneficial to improving the capacity and first coulombic efficiency of the battery.
[0175] In some embodiments, the gas flow ratio of the protective gas to the silicon source gas is 85:15 to 75:25.
[0176] The above range is beneficial to improving the battery cycle performance.
[0177] In some embodiments, the insulation reaction time is 8 hours to 16 hours.
[0178] Optionally, the insulation reaction time is 10 to 16 hours.
[0179] The above range is conducive to the battery having high capacity, better cycle stability and high first coulombic efficiency.
[0180] In some embodiments, the preparation method further includes: using the product obtained by depositing silicon particles on porous carbon as a body, placing the body in a mixed atmosphere of a carbon source and an inert gas, and pyrolyzing the carbon source to form a carbon coating layer coated on the body, wherein the carbon source includes one or more of alkanes, alkynes and alkenes.
[0181] Inert gases include, but are not limited to, nitrogen or argon.
[0182] Alkanes include but are not limited to methane, alkenes include but are not limited to ethylene, and alkynes include but are not limited to acetylene.
[0183] Through the above-mentioned setting method, a carbon coating layer can be formed on the surface of the main body. The setting of the carbon coating layer can reduce the specific surface area to improve the material interface stability and alleviate the problem of the first coulomb efficiency loss caused by the oxidation of silicon dioxide on the surface of the material.
[0184] If the temperature of the pyrolysis carbon source is too low, the carbon source cannot be decomposed and effectively coated on the surface of the body; if the temperature is too high, the deposited silicon particles and porous carbon will react to form silicon carbide, resulting in material capacity loss. If the time of pyrolysis carbon source is too short, the carbon coating amount is too small, and it cannot completely cover the surface of the body to achieve the purpose of reducing the specific surface area; in order to ensure the coating effect, the carbon coating temperature is at a relatively high level, and there is a risk of generating silicon carbide at this temperature. Therefore, if the coating time is too long, it is easy to promote the formation of silicon carbide, thereby causing capacity loss.
[0185] In some embodiments, the temperature of pyrolyzing the carbon source is 400° C. to 800° C., and the pyrolysis time is 0.2 h to 2 h.
[0186] By controlling the temperature of the pyrolysis carbon source and the pyrolysis time, the carbon coating layer can completely cover the surface of the body to reduce the specific surface area and alleviate the formation of silicon carbide, thereby effectively improving the capacity and cycle performance of the battery.
[0187] Illustratively, the temperature of the pyrolyzed carbon source is any one of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or between any two values.
[0188] Exemplarily, the pyrolysis time is any one of 0.2 h, 0.5 h, 0.7 h, 1 h, 1.2 h, 1.5 h, 1.7 h, 2 h, or between any two values.
[0189] In some embodiments, the gas flow ratio of the inert gas to the carbon source is 1:(1.5-5).
[0190] By controlling the gas flow ratio of inert gas to carbon source within the above range, on the one hand, the coating efficiency is effectively improved, and on the other hand, it is convenient to control the decomposition rate of the carbon source and alleviate its local enrichment, which is beneficial to obtain a coating layer with uniform thickness and improve the battery's cycle performance and first coulomb rate.
[0191] According to some embodiments of the present application, the present application also provides a negative electrode plate, comprising the silicon-carbon negative electrode material of any of the above schemes.
[0192] According to some embodiments of the present application, the present application also provides a battery, comprising a negative electrode plate of any of the above schemes.
[0193] According to some embodiments of the present application, the present application also provides an electrical device, which includes a battery according to any of the above schemes, and the battery is used to provide electrical energy.
[0194] Some specific embodiments are listed below to better illustrate the present application.
[0195] In the following embodiments and comparative examples, the relevant parameters of porous carbon are determined as follows:
[0196] [Average pore size, pore volume and micropore ratio of porous carbon]
[0197] The pore size is tested by gas adsorption method according to GB / T19587-2017 & GB / T21650.2-2008 test standards, as follows: porous carbon is taken as a sample, the sample tube is immersed in liquid nitrogen at -196°C, nitrogen is adsorbed on the material to be tested at a relative pressure of 0 to 1, and the pore size distribution and pore volume of the porous material are characterized based on the relationship between the volume of each pore size and the corresponding partial pressure.
[0198] The micropore fraction can be calculated based on the pore size distribution of the porous material.
[0199] [Specific surface area of porous carbon]
[0200] The specific surface area is tested by the gas adsorption method according to the GB / T19587-2017 test standard, as follows: porous carbon is taken as a sample, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05 to 0.30. The monolayer adsorption amount of the sample is obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the solid.
[0201] BET formula:
[0202]
[0203] n a - amount of adsorbed gas, in mol / g; P / P0-relative pressure; n m -Monolayer adsorption capacity.
[0204] Example 1
[0205]
Silicon-carbon anode material
[0206] (1) The porous carbon shown in Table 1 is placed in a heating chamber of a vapor deposition furnace, and the heating chamber is evacuated using a vacuum pump.
[0207] (2) Nitrogen is introduced into the heating chamber. After the protective gas fills the heating chamber, a mixed gas is introduced at a gas flow ratio of nitrogen to silane gas of 85:15. While introducing the mixed gas, the heating chamber is heated to 460°C to decompose silane into silicon, which is deposited in the pores of the porous carbon. The mixed gas is continuously introduced into the heating chamber, and the pressure in the heating chamber is maintained at normal pressure. The heating chamber is kept warm for 12 hours to obtain the body.
[0208] (3) In a nitrogen atmosphere, the heating chamber is first heated to 660°C, and then acetylene gas is used as a carbon source, and a mixed gas is introduced at a gas flow ratio of nitrogen to acetylene gas of 1:2. The heating chamber is kept warm for 0.5 h, and a carbon coating treatment is performed on the surface of the body to obtain a silicon-carbon negative electrode material. The synthesis process of the silicon-carbon negative electrode material is shown in Table 1.
[0209]
Performance test
[0210] (1) Silicon particle crystallinity
[0211] The crystallinity is calculated by dividing the area of the Raman peak representing the crystalline silicon in the silicon particle by the area of the Raman peak representing the entire silicon including the crystalline phase and the amorphous phase in the silicon particle.
[0212] (2) XRD test and average grain size calculation
[0213] According to the JIS / K0131-1996 test standard, the XRD pattern of the sample is tested. According to the XRD pattern of the sample, the half-peak width β and the diffraction angle θ of the Si (111) crystal plane diffraction peak are taken and substituted into the Debye-Scherrer formula to calculate the particle size of the nano-silicon grains. Debye-Scherrer formula: Dhkl = kλ / βcosθ, where Dhkl-the particle size of the nano-silicon grains, in nm; k-Scherrer constant, 0.89; λ-the wavelength of the incident X-ray, 0.15406nm; β-the half-peak width of the diffraction peak, in rad; θ-the diffraction angle, in degrees.
[0214] (3) Silicon content test
[0215] The silicon content was determined by emission spectroscopy (Inductively coupled plasma, ICP) as follows: a carbon-silicon complex was taken as a sample, the sample was digested with aqua regia and hydrofluoric acid HF, and the silicon content of the solution after digestion was tested.
[0216] (4) Porosity test of silicon-carbon negative electrode materials
[0217] Tested according to GB / T24586 test standard, porosity P = (V2-V1) / V2*100%, apparent volume V2 = S*H*A, where: S-area, cm 2; H-thickness, cm; A-sample number, EA; V1-true volume of sample, cm 3 ; V2-apparent volume of sample, cm 3 .
[0218] (5) Battery preparation and related performance testing
[0219]
Preparation of positive electrode sheet
[0220] The 811 type high nickel ternary material (Li(Ni 0.8 Co 0.1 Mn 0.1 )O2), conductive agent acetylene black, binder PVDF (polyvinylidene fluoride) are mixed in a weight ratio of 94:4:2, and solvent N-methyl pyrrolidone is added, and the mixture is stirred and mixed to obtain positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying and cold pressing.
[0221]
Preparation of negative electrode sheet
[0222] The silicon-carbon negative electrode material, conductive agent acetylene black, binder SBR (styrene-butadiene rubber), and thickener CMC-Na (sodium carboxymethyl cellulose) prepared in each embodiment and comparative example were mixed at a weight ratio of 95:1.5:3.1:0.4, and deionized water was added as a solvent, and the mixture was stirred and mixed to obtain a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0223]
Preparation of electrolyte
[0224] Weigh 0.6122 g of sodium perchlorate and add it to 10 ml of propylene carbonate solvent, stir until the sodium perchlorate is completely dissolved, then add 3% by mass of fluoroethylene carbonate as an additive, stir thoroughly and use it as an electrolyte.
[0225]
Provide isolation film
[0226] A polyethylene porous membrane was used as the isolation membrane.
[0227]
Assembly button battery
[0228] The negative electrode sheet, the isolation film, and the lithium metal sheet as the positive electrode prepared above are stacked in order, so that the isolation film is placed between the negative electrode sheet and the lithium metal sheet to play an isolating role, the isolation film is soaked with the electrolyte prepared above, and then compacted to obtain a button battery.
[0229]
Assembly of full battery
[0230] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound and placed in an outer package, and the prepared electrolyte is injected and packaged, injected, formed, vented, and other processes are performed to obtain a lithium-ion battery.
[0231] Those skilled in the art will appreciate that, in the above methods of the specific embodiments and comparative examples, the order in which the steps are written does not imply a strict order of execution and does not constitute any limitation on the implementation process, and the specific order of execution of the steps should be determined by their functions and possible internal logic.
[0232] [First coulombic efficiency test of button cell]
[0233] Test process: Under normal temperature conditions, let the battery stand for 3 hours, then discharge at a constant current of 0.05C to a voltage of 0.005V, and further discharge at a constant current of 50μA to a voltage of 0.005V, and record the capacity at this time as the lithium insertion capacity. Let stand for 5 minutes, and then charge at a rate of 0.1C to a voltage of 2V, and record the capacity at this time as the lithium removal capacity.
[0234] The first coulombic efficiency of silicon-carbon negative electrode material (%) = (lithium removal capacity / lithium insertion capacity)*100%.
[0235]
Full battery cycle performance and first discharge capacity test
[0236] Normal temperature cycle performance test:
[0237] Test conditions: Under normal temperature, the battery was left to stand for 30 minutes, then charged at a rate of 0.5C to a voltage of 4.2V, further charged at a constant voltage of 4.2V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a rate of 0.5C to a voltage of 2.8V. This is a charge and discharge cycle. The discharge capacity was recorded at each cycle, and the capacity retention rate after n cycles (%) = (discharge capacity of the nth cycle / discharge capacity of the first cycle) × 100%. When the discharge capacity of the battery decayed to 80% of the discharge capacity of the first cycle, the test was stopped and the number of cycles of the battery was recorded.
[0238] The test results are shown in Table 3.
[0239] Examples 2 to 17 and Comparative Examples 1 to 2
[0240] The differences between the porous carbon in each embodiment and comparative example and embodiment 1 are shown in Table 1, the differences in preparation process parameters are shown in Table 1, and the test results of the prepared silicon-carbon negative electrode material and the assembled battery are shown in Table 2.
[0241] Table 1 Selection and preparation process parameters of porous carbon
[0242]
[0243]
[0244] In Table 1, nitrogen:silane refers to the gas flow ratio of nitrogen to silane, and nitrogen:acetylene refers to the gas flow ratio of nitrogen to acetylene.
[0245] Table 2 Test results
[0246]
[0247] From Table 1 and Table 2, it can be seen that the silicon-carbon negative electrode material provided in the embodiment of the present application has a crystalline phase in the silicon particles and a crystallinity of at least 90%. Under the condition that the average grain size of the silicon particles is less than 4 nm, when it is applied to a battery, the battery has high capacity, better cycle stability and high first coulombic efficiency.
[0248] According to Examples 1 and 2, since Example 2 is not carbon-coated, the BET of the silicon-carbon negative electrode material prepared in Example 2 is slightly larger than that in Example 1, and since it is not carbon-coated, a certain amount of silicon oxide exists on the surface of the silicon-carbon negative electrode material prepared in Example 2, and silicon oxide consumes active lithium and has no reversible capacity, thus causing its capacity and first efficiency to be lower than those in Example 1, and the cycle performance is also slightly lower than that in Example 1 due to the influence of the first efficiency.
[0249] According to Examples 1, 3, and 4, the main difference between the products of Examples 3 and 4 and those of Example 1 is the enlargement of silicon grains and the reduction of porosity. Therefore, compared with Example 1, the cycle performance of Examples 3 and 4 is slightly worse under the premise of similar capacity and first effect.
[0250] According to Examples 1 and 5 to 8, when the silicon deposition temperature is 400°C to 550°C, especially 430°C to 530°C, when the prepared silicon-carbon negative electrode material is used in a battery, the battery has high capacity, better cycle stability and high first coulombic efficiency.
[0251] According to Examples 1, 9 to 11, when the gas flow ratio of the protective gas to the silicon source gas is 90:10 to 70:30, the battery has better capacity, coulombic efficiency and cycle performance.
[0252] According to Examples 1, 12, and 13, it can be seen that the deposition time affects the crystallinity and the cycle performance. In Example 12, the deposition time is reduced, so the amount of silicon deposition is small, and under the same other process conditions, it can be seen that the crystallinity increases slightly with the increase of the deposition time. The capacity is reduced due to the decrease in crystallinity, which leads to a decrease in the first efficiency. The expansion is low due to the low first efficiency but high porosity, thereby improving the cycle performance. Compared with Example 1, Example 13 has a slightly higher crystallinity, which improves its capacity, mainly due to the increase in deposition time, but because the porosity is lower than that of Example 1, there is a cycle deviation.
[0253] According to Examples 1, 14 to 15, the carbon coating temperature (that is, the temperature of the pyrolysis carbon source) affects the first efficiency and cycle performance of the battery. In Example 14, the carbon coating temperature is 800°C. Since the coating temperature is increased compared to Example 1, the decomposition efficiency of acetylene is improved, which leads to a decrease in the percentage of silicon and a decrease in BET. However, the increase in coating temperature leads to an increase in crystallinity, and the orientation of silicon grain expansion is stronger, that is, the overall expansion of the silicon-carbon negative electrode material increases, so the cycle performance is slightly lower than that of Example 1. In Example 15, due to the excessively high carbon coating temperature, silicon carbide is generated, resulting in a loss of the first discharge capacity and first efficiency of the battery, and the excessively high temperature also leads to a further increase in crystallinity, and the cycle is also slightly deteriorated.
[0254] According to Examples 1 and 16 to 17, the gas flow ratio during the carbon coating process mainly affects the thickness of the carbon coating layer on the surface of the finished product. When the gas flow ratio of the inert gas to the carbon source is 1:(1.5 to 5), as the acetylene gas flow rate increases, the thickness of the carbon coating layer increases, and the BET decreases. Affected by the increase in the carbon coating layer, the silicon content decreases slightly, and it has little effect on the capacity, first effect, porosity, crystallinity, etc., and the cycle is basically unaffected.
[0255] Since nano silicon particles are easy to agglomerate, if there is no framework restriction, nano silicon particles can grow freely without restriction. Therefore, according to Example 1 and Comparative Example 1, since the average pore size of porous carbon in Comparative Example 1 is large and the micropores are few, the average silicon grain size in the final product is larger under the same deposition conditions. The large grain size will increase the difference in silicon expansion force in all directions, resulting in a significant reduction in the number of cycles. In addition, since the carbon substrate of Comparative Example 1 has more mesopores and macropores, while ensuring the same porosity level, Comparative Example 1 is less pressure-resistant, and the material partially cracks during the cold pressing process, resulting in a low first efficiency of the battery.
[0256] According to Example 1 and Comparative Example 2, in Comparative Example 2, due to the silicon deposition parameters during the silicon deposition process, amorphous silicon is generated, resulting in a significant reduction in the first effect.
[0257] in, Figure 5 XRD diagram of the silicon-carbon negative electrode material provided in Example 1; Figure 6 XRD diagram of the silicon-carbon negative electrode material provided in Comparative Example 1; Figure 7 This is the XRD diagram of the silicon-carbon negative electrode material provided for Comparative Example 2.
[0258] Comparative Example 1 deposits crystalline silicon, and the silicon grain size is larger than that of Example 1, so the peak between 28 and 29° is sharper. Comparative Example 2 deposits amorphous silicon, and XRD shows characteristic peaks of the carbon substrate, which are bulge-shaped, especially the top of the first bulge is smooth. Because Example 1 has crystalline silicon and the silicon grain size of Example 1 is small, the characteristic peak of silicon is partially covered by the peak of porous carbon, so its first peak is slightly sharper than that of Comparative Example 2.
[0259] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The invention comprises porous carbon and silicon particles attached to the pore walls of the porous carbon, wherein the silicon particles contain a crystalline phase and have a crystallinity of at least 90%, and the average crystal size of the silicon particles is less than 4 nm.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The average grain size of the silicon particles is less than 2 nm.
3. The silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The average pore diameter of the porous carbon is ≤4 nm, and can be optionally ≤2 nm.
4. The silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The porous carbon satisfies at least one of the following characteristics: (a1) The porous carbon has micropores, mesopores and macropores, and the volume proportion of the micropores is ≥75%; (a2) The specific surface area of the porous carbon is ≥ 1700 m 2 / g; (a3) The pore volume of the porous carbon is ≥ 0.75 m 3 / g; Optionally, the porous carbon satisfies at least one of the following characteristics: (b1) The porous carbon has micropores, mesopores and macropores, and the volume proportion of the micropores is ≥85%; (b2) The specific surface area of the porous carbon is ≥ 1800 m 2 / g; (b3) The pore volume of the porous carbon is ≥ 0.8 m 3 / g.
5. The silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The porous carbon and the silicon particles are used together as a main body, and the silicon-carbon negative electrode material further includes a carbon coating layer coated on the main body.
6. The silicon-carbon negative electrode material according to claim 5, characterized in that: The carbon coating layer is discontinuously coated, and the thickness of the carbon coating layer is 1 to 40 nm.
7. The silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The silicon-carbon negative electrode material meets at least one of the following characteristics: (c1) The mass content of the silicon particles in the silicon-carbon negative electrode material is 35-55%; (c2) the porosity of the silicon-carbon negative electrode material is 40% to 60%; (c3) The specific surface area of the silicon-carbon negative electrode material is ≤ 6m 2 / g; (c4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 4 μm to 15 μm.
8. The silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The silicon-carbon negative electrode material meets at least one of the following characteristics: (d1) The mass content of the silicon particles in the silicon-carbon negative electrode material is 40% to 50%; (d2) the porosity of the silicon-carbon negative electrode material is 45% to 55%; (d3) The specific surface area of the silicon-carbon negative electrode material is ≤4m 2 / g; (d4) The volume particle size distribution Dv50 of the silicon-carbon negative electrode material is 5 μm to 10 μm.
9. A method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 8, characterized in that: include: Depositing the silicon particles on the porous carbon by chemical vapor deposition; Wherein, the average pore diameter of the porous carbon is ≤4nm.
10. The preparation method according to claim 9, characterized in that: The method of depositing the silicon particles on the porous carbon by chemical vapor deposition includes: Placing the porous carbon in a reaction atmosphere, and keeping the temperature at 400° C. to 550° C. for at least 8 hours, wherein the reaction atmosphere is a mixed atmosphere of a protective gas and a silicon source gas, the gas flow ratio of the protective gas to the silicon source gas is 90:10 to 70:30, and the protective gas includes at least one of an inert gas and hydrogen; Optionally, the temperature of the insulation reaction is 430°C to 530°C; Optionally, the gas flow ratio of the protective gas to the silicon source gas is 85:15 to 75:25; Optionally, the insulation reaction time is 8 hours to 16 hours, and optionally 10 hours to 16 hours.
11. The preparation method according to claim 9 or 10, characterized in that: The preparation method further comprises: using the product obtained by depositing the silicon particles on the porous carbon as a body, placing the body in a mixed atmosphere of a carbon source and an inert gas, and pyrolyzing the carbon source to form a carbon coating layer coated on the body; Wherein, the carbon source includes one or more of alkanes, alkynes and alkenes; Optionally, the temperature for pyrolyzing the carbon source is 400° C. to 800° C., and the pyrolysis time is 0.2 h to 2 h; Optionally, the gas flow ratio of the inert gas to the carbon source is 1:(1.5-5).
12. A negative electrode plate, characterized in that: It comprises the silicon-carbon negative electrode material as described in any one of claims 1 to 8.
13. A battery, characterized in that: It includes the negative electrode sheet as claimed in claim 12.
14. An electrical device, characterized in that: It comprises a battery as claimed in claim 13, wherein the battery is used to provide electrical energy.
Citation Information
Patent Citations
Negative active material for lithium secondary battery method of manufacturing the same and lithium secondary battery including the same
CN109285997A
Electrochemical device and electronic device
CN114420998A
Negative electrode material, negative electrode plate and battery
CN116053447A
Negative active material, method for preparing same, and secondary battery and electric device comprising same
CN116888753A
Producing an electrically conductive porous carbon material useful as a battery anode material comprises incorporating silicon and / or tin nanoparticles into a polymer matrix and carbonizing the product
DE102009033251A1
Cited By
Silicon-carbon composite negative electrode material for lithium ion battery and preparation method of silicon-carbon composite negative electrode material
CN120109182A
Silicon-carbon composite negative electrode material for lithium-ion battery and preparation method thereof
CN120109182B
Silicon-carbon negative electrode material, secondary battery and electronic equipment
CN120958597A
Silicon-carbon negative electrode material, preparation method therefor, negative electrode piece, electrode, and electric device
EP4800766A1